INFORMAL INSTITUTIONS, GOVERNMENT REGULATORY FUNCTIONS, AND DEVELOPMENT OF GOVERNANCE STUDIES - Pitono, Andi; Harahap, Agus Supriadi; Kartiwi, Kartiwi; Baidhowah, Adfin R. (Jurnal Politik Pemerintahan Dharma Praja, 2023)
The debate over governance studies in the 1980s and 1990s revolved around the dichotomy between governance studies as an autonomous scientific field and governance studies as a component of political or administrative study. During the present decade, the field of government has undergone significant axiological advancements. This article seeks to establish a theory in the field of governance studies that specifically examines one of the roles of government. It does so by presenting empirical evidence of non-litigation case resolution and highlighting the function of legal professionals at the village level. These professionals serve as the primary representatives of the government and directly interact with the community. The utilization of qualitative methodologies reveals that the resolution of non-litigation cases and the involvement of legal entities at the village level are primarily dependent on the interactions between village heads and informal institutions, such as religious leaders, traditional leaders, and community leaders. These interactions serve as the key components in resolving non-litigation disputes, thereby establishing a supplementary institution. Hence, there exists a conceptual correlation between informality and governance studies based on empirical evidence on the operation of informal arrangements and institutions. This essay aims to enhance the development of governance studies by acknowledging the prevalent issue of high informality in Indonesia. In order to establish a new theory in governance studies known as government informality, it is necessary to explore the relationship between governance studies and the concept of informality. Government informality refers to the collaboration between government regulatory responsibilities performed by government officials and informal institutions within society to address social issues.